A Reasoned Action Approach to Depression Help-Seeking Messaging for College Students: Implications of Cognitive Biases in Depression. Issue 14 (6th December 2022) - Yzer, Marco; Kinzer, Hannah; Malone, Molly
ABSTRACT: In this study we integrated insights from research on cognitive biases in depression with the reasoned action approach to predicting and changing behavior (RAA) with the goal of identifying implications for help-seeking messaging for college students with varying levels of depression. Findings from a sample of 374 U.S. college students support the ability of RAA to explain help-seeking intentions for non-depressed, mildly depressed students, and moderate to severely depressed students. More severe depression was associated with less favorable attitudes, perceived norms, perceived capacity, and intention; changes in the relative strength of attitudes, perceived norms, and perceived capacity in explaining help-seeking intentions; stronger expectations of negative outcomes of help-seeking and weaker expectations of positive outcomes; and to some extent, stronger expectations of negative outcomes for oneself than for others. These findings underscore that depressed students construe help-seeking differently than non-depressed students, and that depressed and non-depressed students need different help-seeking messages.